The Archaeology of the Peasant Land Market in Pre-Plague England c ad 1290–1350: A Way Forward. Issue 2 (16th October 2016) - Platt, Colin
Abstract : WHILE ARCHAEOLOGISTS are well informed about plague and climate change, many are less familiar with the emergence in pre-plague England of a vigorous market in peasant land in which both freemen and villeins were represented. Yet the tenant's growing freedom to buy and sell land arguably played a larger part in transforming the social structure of late-medieval England than either the Black Death ( ad 1348–9) or Great Famine ( ad 1315–17). Accustomed to seeing the five decades before the pestilence as a final interlude of prosperity before the onset of recession, archaeologists have looked chiefly to the post-plague years for evidence of change. However, the toxic combination of a hyperactive peasant land market, combined with the worst subsistence crisis that England has ever known, had encouraged the growth earlier in the century of a rich and increasingly acquisitive and dominant peasant or 'kulak' class with properties it needed to protect. The large and more permanent village house, it is argued here, originated at this time. It is also suggested that it was successful peasant engrossers, rather than status-hungry, would-be gentry, who were probably the diggers of the overwhelming majority of non-manorial moats which survive in such numbers across England. Although more work is needed to date these moats archaeologically, it is already widely assumed that they belong primarily to the first half of the 14th century. If this is correct, the smaller domestic or 'homestead' moat, occurring in multiples of up to 13 in some parishes, can now be seen as persuasive material evidence of a catastrophic crisis in law and order which historians know only from the documentary sources.